Silicon effect on the formation of graphite inclusions in gray cast iron - Ivanov, Valerii; Pirozhkova, Valentina; Lunеv Valentin (Eastern-European Journal of Enterprise Technologies, 2017)
Using conventional and high-temperature metallography, micro-X-ray spectroscopy and mass spectral analyzes, as well as the petrographic method, the study explores the effect of silicon on the morphology of graphite inclusions in gray cast irons. So far, the role of silicon in the theory of graphite formation during the crystallization of cast irons remains unclear. Therefore, the disclosure of the mechanism of the influence of silicon on the formation of graphite inclusions can help fully control the structure and properties of cast iron castings and develop optimal technological processes for their production. It has been established that the reaction in the silicon interaction with carbon monoxide in iron-carbon alloys, leading to the formation of a surface-active silicon monoxide, is caused by the temperature and physicochemical conditions of the melt. In gray cast iron, the rate and intensity of the course of this reaction have a direct effect on the morphology of lamellar graphite. The study has revealed four morphological forms of primary graphite (rosette, rectilinear-plate, ramiform, and vermicular), formed in various physicochemical conditions of the crystallization of gray cast iron